PHYTOCHEMICAL SCREENING AND EVALUATION OF ANTI-INFLAMMATORY ACTIVITY OF AERIAL PART EXTRACTS OF PLANTAGO MAJOR L. - Vandana, Jyoti; K, Gupta A; Mukerjee, Alok (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study aims to perform phytochemical screening and investigate anti-inflammatory activity of extract from aerial part of the plant Plantago major L. Methods: Preliminary phytochemical screening of plant extract was carried out using standard qualitative procedures and anti-inflammatory activity was evaluated using carrageenan-induced paw edema model in male Wistar albino rats using plethysmometer. Diclofenac sodium (10 mg/kg, b.w.) was used as standard drug. Results: Preliminary phytochemical screening of the different extracts revealed that they were rich in secondary metabolite compounds such as carbohydrates, tannins, steroids, flavonoids, terpenoids, glycosides, fats and oils, alkaloids, phenolic compounds, and iridoid glycosides. The anti-inflammatory activity was evaluated using carrageenan-induced paw edema models in Wistar albino rats. The anti-inflammatory activity of methanolic extract (ME) was found to be dose dependent in carrageenan-induced paw edema model. The ME has shown significant (p<0.05) inhibition of paw edema, 61.11% and 55.55% on 4th hr at the doses of 900 and 600 mg/kg, respectively. Conclusion: The results of the present study demonstrate that ME of the aerial parts of the plant possess significant (p<0.05) anti-inflammatory potential.